Ambiente institucional e organização de redes de franquias: uma comparação entre Brasil e França - Silva, Vivian Lara dos Santos (2004)
Franchise companies deal with a classical dilemma: how to reconcile the gains from the expansion of franchising with the potential cost of the brand name misuse by franchisees. This dissertation analysis this question under the institutional background, which differs from one country to another. It intends to explore the role of the formal and informal rules of the game according to NORTH (1990) terminology to institutional environment on the organizational design of franchise companies. To deal with the potential hazards regarding misuse of the valuable asset in a franchise contract, i.e., brand name (RUBIN, 1978), franchise companies should be able to conciliate a better alignment between incentives by franchisees and franchisors to a higher control over franchisees local actions under quality standards. This statement should induce vertical efforts by franchise companies, in terms of interfirm contractual arrangements in both distribution and supply chain management. More than substitutes, these efforts are expected to be complementary. The way that these efforts are combined, however, depends on the rules of the gaime that the companies are embedded, regarding to law (formal rules), as well as culture, social codes, and consumption standards (informal norms) of each coutry. This dissertation presents a comparative analysis of Brazilian and French food franchising. Besides their economic and historical relevance in the international franchising, Brazil and France are embedded in particulars rules of the game, allowing for the discrimination of different institutional environments effect on the franchise companies organization. Based on a standardization interview agenda custom-made for this study, ten cases are addressed. The main empirical results show the complementarities of the vertical efforts and the role of institutional arrangements in the management and control models of brand name value.